Kedudukan Kepala Otorita Ibu Kota Nusantara Dalam Perspektif Hukum Otonomi Daerah - Rizki Mulyaningsih (Universitas Islam Indonesia, 2022)
The government officially promulgated Law Number 3 of 2022 on the State Capital (IKN Law) with the branding of Nusantara as the Capital. There lies a legal issue regarding the position of the Head of the IKN Authority in Article 5 paragraph (4) of the IKN Law. The Head of the IKN Authority is at the ministerial level, selected and appointed by the President. Hence, this study examines: First, how is the position of the Authoritative Head in Law Number 3 of 2022 in terms of the perspective of regional autonomy law? and Second, what are the implications of regulating the position of the Authoritative Head in terms of regional autonomy law? The research method used is juridical-normative with a statutory approach. The results of this study conclude that the regulation of the position of the Head of the IKN Authority is still centralized and is not in accordance with the 1945 Constitution of the Republic of Indonesia. The implications of this rule when viewed from the regional autonomy law, namely the election and dismissal of the Head of the IKN Authority is a privilege of the President, is centralized, and there is no Regional House of Representatives as an instrument of regional autonomy.Key Words: State capital; head of authority; regional autonomy AbstrakPemerintah resmi mengundangkan Undang-Undang Nomor 3 Tahun 2022 tentang Ibu Kota Negara (UU IKN) dengan branding Ibu Kota Nusantara. Terdapat persoalan terkait kedudukan Kepala Otorita IKN dalam Pasal 5 ayat (4) UU IKN. Persoalannya yaitu Kepala Otorita IKN berkedudukan setingkat menteri, ditunjuk, dan diangkat oleh Presiden. Maka, penelitian ini mengkaji: Pertama, bagaimana kedudukan kepala otorita dalam Undang-Undang Nomor 3 Tahun 2022 ditinjau dari perspektif hukum otonomi daerah? dan Kedua, bagaimana implikasi pengaturan kedudukan kepala otorita ditinjau dari hukum otonomi daerah? Metode penelitian yang digunakan yuridis-normatif dengan pendekatan perundang-undangan. Hasil penelitian ini menyimpulkan bahwa pengaturan kedudukan kepala otorita IKN masih bersifat sentralisasi dan belum sesuai dengan UUD NRI 1945. Implikasi aturan tersebut jika ditinjau dari hukum otonomi daerah, yaitu pemilihan dan pemberhentian Kepala Otorita IKN merupakan hak istimewa Presiden, bersifat sentralisasi, dan tidak ada DPRD sebagai instrumen otonomi daerah.Kata-kata Kunci: Ibu kota negara; kepala otorita; otonomi daerah